VD_FINDINFO HC / 2010 / 231 vom 9. Februar 2010 - VD Tribunal cantonal (2010)
CONTRIBUTION PATRIMONIALE DU CONJOINT, DIVORCE, CONTRIBUTION EXTRAORDINAIRE D'UN ÉPOUX | 138 al. 1 CC, 165 al. 1 CC, 165 CC, 452 al. 1ter CPC, 452 al. 2 CPC, 452 CPC